Guidelines for approaching trans children and adolescents at primary care level (Archives of Pediatrics of Uruguay, 2023)
Introduction: many times pediatricians or family doctors are the first people trans-children and adolescents consult and raise questions and experiences to. Therefore, it is key for doctors to have an unbiassed approach to this issue in the consultation, with an updated view of the framework of children and adolescents.Objective: provide tools for proper health care support and follow-up ifor trans children and adolescents at primary care.Methodology: for the preparation of these guidelines, we made a bibliographic review in Pubmed, Scielo. This search was carried out from 2010 to date using “trans children”, “trans adolescents” prescribers, in English and in Spanish.Results: guidelines were created for primary care regarding the care of trans children and adolescents, providing tools for medical records and considering the interview, the physical examination and the multi-interdisciplinary approach.Conclusions: trans experiences in childhood and adolescence should not be viewed from a pathologizing perspective, but rather as legitimate experiences. Health professionals play a key role in accompanying and guarding the rights of children and adolescents and promoting their autonomy in decision-making instances.
Keywords: Transsexualism; Transgender; Child; Adolescent